Structure and Function Analysis of an Antibody Recognizing All Influenza A Subtypes - Kallewaard, Nicole L; Corti, Davide; Collins, Patrick J; Neu, Ursula; McAuliffe, Josephine M; Benjamin, Ebony; Wachter-Rosati, Leslie; Palmer-Hill, Frances J; Yuan, Andy Q; Walker, Philip A; Vorlaender, Matthias K; Bianchi, Siro; et al. (Cell, 2016)
Influenza virus remains a threat because of its ability to evade vaccine-induced immune responses due to antigenic drift. Here, we describe the isolation, evolution, and structure of a broad-spectrum human monoclonal antibody (mAb), MEDI8852, effectively reacting with all influenza A hemagglutinin (HA) subtypes. MEDI8852 uses the heavy-chain VH6-1 gene and has higher potency and breadth when compared to other anti-stem antibodies. MEDI8852 is effective in mice and ferrets with a therapeutic window superior to that of oseltamivir. Crystallographic analysis of Fab alone or in complex with H5 or H7 HA proteins reveals that MEDI8852 binds through a coordinated movement of CDRs to a highly conserved epitope encompassing a hydrophobic groove in the fusion domain and a large portion of the fusion peptide, distinguishing it from other structurally characterized cross-reactive antibodies. The unprecedented breadth and potency of neutralization by MEDI8852 support its development as immunotherapy for influenza virus-infected humans.